Prevalence of behavioral risk factors, overweight and hypertension in the urban slums of North 24 Parganas District, West Bengal, India, 2010 - Tushar Acharyya; Prabhdeep Kaur; Manoj V Murhekar (Wolters Kluwer Medknow Publications, 2014)
Globally, 1 billion people live in slums. There are few reports of high prevalence of noncommunicable disease (NCD) risk factors among the urban poor. The prevalence of NCD risk factors in the slums in North 24 Parganas, West Bengal, India was estimated. Cross-sectional survey in 24 slums selected using cluster sampling method was conducted. Questionnaire for behavioral risk factors was used and anthropometric and blood pressure measurements were done. The study population included 1052 participants aged 25-64 years, 528 (50%) were males. Among males, 206 (39%) were current smokers and 154 (29%) were current alcohol users. Central obesity was prevalent among 32.8% males and 56.1% females and 115 (10.9%) had body mass index ≥27.5 kg/m 2 . Hypertension was prevalent among 35% males and 33% females. We observed high prevalence of NCD risk factors among urban slum dwellers that need to be addressed with health promotion programs and strengthening of primary health care system.